2014
DOI: 10.1016/j.celrep.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Antivirulence Properties of an Antifreeze Protein

Abstract: In the originally published version of this article, the authors neglected to include the following paragraph in the Experimental Procedures:''Mice were monitored at regular intervals for up to 36 hr for the following signs of moribund condition: sustained hypothermia (body temperature < 30 C for more than 1 hr, as measured by the infrared thermometer), lethargy, dehydration, change in color of mucous membranes, and labored breathing. We determined that mice showing more than three of the indicated signs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…We adjusted the timing of the first dose of imipenem/cilastatin from 1 to 6 h postoperative to maintain a mortality rate of 30-60% throughout the duration of the study. For the experiment comparing C57BL/6J, IRF3-KO (original), and IRF3-KO (backcrossed) mice, we used the severe model of sepsis described in our prior studies (21,(23)(24)(25).…”
Section: Sepsis Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We adjusted the timing of the first dose of imipenem/cilastatin from 1 to 6 h postoperative to maintain a mortality rate of 30-60% throughout the duration of the study. For the experiment comparing C57BL/6J, IRF3-KO (original), and IRF3-KO (backcrossed) mice, we used the severe model of sepsis described in our prior studies (21,(23)(24)(25).…”
Section: Sepsis Modelmentioning
confidence: 99%
“…A genome scan revealed that the backcrossed mice were 96.9% congenic to C57BL/6J strain. To get an expedient answer using the minimum number of animals, we performed the severe CLP model described in our prior reports (21,(23)(24)(25). We induced severe CLP in the IRF3-KO (backcrossed) mice alongside the IRF3-KO (original) mice and C57BL/6J controls.…”
Section: An Irf3-deficient Host Environment Attenuates Il-6 Production By Adoptively Transferred Monocytesmentioning
confidence: 99%
“…A la fecha, no es claro cómo la bacteria penetra y coloniza el intestino medio de la garrapata, ni mucho menos, los mecanismos moleculares asociados. Sin embargo, se ha demostrado que la glicoproteína anticoagulante IAFGP de I. scapularis, es capaz de inhibir la formación de las biopelículas bacterianas (Heisig et al, 2014). Interesantemente, la bacteria A. phagocytophilum, secuestra a la proteína IAFGP, con el fin de alterar su acumulación en el intestino medio de las garrapatas para inhibir el desarrollo de biopelículas, permitiendo así su colonización y establecimiento en el vector (Heisig et al, 2014).…”
Section: Estudio Del Microbioma En Garrapatasunclassified
“…Microbial biofilms (6), generated by diverse bacterial species, are essential for bacterial colonization microbiota favoring the abundance of strong biofilm formers. Results demonstrate that communities of bacteria are functionally redundant, suggesting a mechanism by ticks selecting the adequate microbiome fulfilling a core set of functions.…”
Section: Introductionmentioning
confidence: 99%